2006
DOI: 10.1152/ajpheart.01254.2005
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of intermediate-conductance Ca2+-activated K+channel (IKCa1) mediates phenotypic modulation of coronary smooth muscle

Abstract: A hallmark of smooth muscle cell (SMC) phenotypic modulation in atherosclerosis and restenosis is suppression of SMC differentiation marker genes, proliferation, and migration. Blockade of intermediate-conductance Ca(2+)-activated K(+) channels (IKCa1) has been shown to inhibit restenosis after carotid balloon injury in the rat; however, whether IKCa1 plays a role in SMC phenotypic modulation is unknown. Our objective was to determine the role of IKCa1 channels in regulating coronary SMC phenotypic modulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
128
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(145 citation statements)
references
References 52 publications
(86 reference statements)
12
128
1
1
Order By: Relevance
“…These results are consistent with the sustained expression of miR145 following TGF-␤1 treatment versus only transient MYOCD mRNA induction. Clearly, the transcriptional and post-transcriptional regulation of MYOCD mRNA warrants deep analysis to uncover its positive regulation by TGF-␤1 as well as its well known reduction in expression under conditions of SMC phenotypic adaptation (4,55,56).…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the sustained expression of miR145 following TGF-␤1 treatment versus only transient MYOCD mRNA induction. Clearly, the transcriptional and post-transcriptional regulation of MYOCD mRNA warrants deep analysis to uncover its positive regulation by TGF-␤1 as well as its well known reduction in expression under conditions of SMC phenotypic adaptation (4,55,56).…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of K Ca 3.1 channels has been found to promote excessive VSMC proliferation and migration induced by either mitogens (platelet-derived growth factor and EGF) or balloon catheter injury. [13][14][15] However, it is unknown whether AGEs is involved in the K Ca 3.1 channel regulation. In the present study, we demonstrated that AGE-BSA increased K Ca 3.1 current density and enhanced K Ca 3.1 channel protein expression in AGEs and K Ca 3.1 channels Li-Mei Zhao et al cultured rat VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…K Ca 3.1 channels are the predominant Ca 2 þ -activated K þ channels in proliferative smooth muscle cells but not in mature contractile cells. [11][12][13][14] The expression of K Ca 3.1 channels is increased in VSMCs in coronary arteries from patients and in aortas of ApoE À / À mice with atherogenesis, and K Ca 3.1 channel blocker markedly slows down the development of atherosclerosis in ApoE À / À mice. 16 However, reports related to the regulation of K Ca 3.1 channels are limited in diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations